Kin1 Kinase Localizes at the Hyphal Septum and is Dephosphorylated by Calcineurin but is Dispensable for Septation and Virulence in the Human Pathogen Aspergillus fumigatus - Juvvadi, Praveen R. (Biochem Biophys Res Commun, 2018)
Studies in yeasts have implicated the importance of Kin1 protein kinase, a member of the eukaryotic PAR1/MARK/MELK family, in polarized growth, cell division and septation through coordinated activity with the phosphatase, calcineurin. Kin1 is also required for virulence of the fungal pathogens Cryptococcus neoformans and Fusarium graminearum. Here we show that kin1 deletion in the human fungal pathogen Aspergillus fumigatus does not affect hyphal growth and septation but results in differential susceptibility to antifungals targeting the cell wall and cell membrane. The ∆kin1 strain remained virulent in a Galleria mellonella model of invasive aspergillosis. Expression of Kin1 tagged to GFP or RFP showed its stable localization at the septum. Co-localization experiments revealed calcineurin (CnaA) localization on either side of Kin1 at the septum suggesting possible interaction. Bimolecular fluorescence complementation assay confirmed the interaction of Kin1 with CnaA at the hyphal tips and septa in the presence of the antifungal caspofungin. Furthermore, phosphoproteomic analyses for the first time revealed Kin1 as a substrate of calcineurin providing novel insight into Kin1 regulation through calcineurin-mediated dephosphorylation mechanism.